Re-evaluating the choice of gamma stimulation frequency for the potential treatment of Alzheimer's disease: Novel invisible spectral flicker evokes gamma responses at various frequencies. - Mark Alexander Henney; Bianca Laura Hansen; Luna Skytte Hansen; Manja Gersholm Grønberg; Martin William Thorning-Schmidt; Henrik Enggaard Hansen; Mai Nguyen; Paul Michael Petersen; Line Katrine Harder Clemmensen; Marcus Carstensen; Kristoffer Hougaard Madsen (PLoS ONE)
With recent advances in the potential usage of visual gamma stimulation at 40 Hz for the treatment of Alzheimer's disease, there is motivation to evaluate adjacent frequencies to ensure that specifically 40 Hz is optimal. As visual stimulation with luminance flicker may affect adherence in clinical trials due to its inherent perceived flickering, invisible spectral flicker (ISF) was proposed as a more comfortable alternative for entraining 40 Hz. Based on current understanding of the potential mechanism of action for 40 Hz stimulation, the exact frequency is debatable. This study investigates the ability of ISF to evoke acute gamma responses at several frequencies in the range of 36-44 Hz. Twenty healthy volunteers were included in an electroencephalography (EEG) experiment with ISF stimulation at nine different frequencies (36-44 Hz, 1 Hz interval). Estimated signal-to-noise ratios (SNR) showed that the cortical power was significantly increased at all stimulation frequencies compared to baseline, but with no significant difference in SNR between stimulation frequencies. There was a significant subject effect, suggesting that there is higher variability between subjects than between frequencies alone. Our results indicate that ISF can evoke steady-state potentials at several frequencies in the low gamma range of 36-44 Hz. Across the population of participants, no preference or trend for any specific gamma stimulation frequency in the tested range was found. While the subject-stimulus interaction was significant, it described little variance and showed no specific patterns for individual preference of frequency.